Dialogue Writing for Dubbing An Insider's Perspective - Spiteri Miggiani, Giselle; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book analyses an important phase in the interlingual dubbing process of audiovisual productions: the elaboration of target language scripts for the recording studios. Written by a practitioner in the industry who is also an academic and trainer, it provides practical know-how and guidelines while adopting a scholarly, structural and methodical approach. Supported by an exemplified, analytical and theoretical framework, it is non-language specific and discusses strategies and tricks of the trade. Divided into three parts, the book provides a descriptive, practical and analytical approach to dubbing and dialogue writing. The author analyses scripts drawn from her own professional practice, including initial drafts that illustrate the various transformations of a text throughout the rewriting process. She also provides a 'backstage' perspective, from first-hand experience in recording sessions that provided first-hand knowledge of text manipulation, studio jargon, and the dubbing post production process. This publication will provide a valuable resource for novice dubbing translators and dialogue writers, while offering practitioner insights to scholars and researchers in the field of Audiovisual Translation, Film and Media Studies. .
Part I: The Dialogue Writing Practice: A descriptive approach -- Chapter 1: Dialogue writing set in context -- Chapter 2: Bridging disciplines: analogies and applicable devices -- Part II: Strategies and Know-how: A practical approach -- Chapter 3: Dialogue Writing Itinerary -- Chapter 4: Dubbing Deliverables -- Chapter 5: Script components -- Chapter 6: Standards and practices -- Part III: Black Box Revealed: An analytical approach -- Chapter 7: Applied strategies.
Keywords: Translating and interpreting; Motion pictures; Motion picture industry; Television broadcasting; Communication; Popular Culture; Language Translation; Audio-Visual Culture; Film and Television Industry; Media and Communication; Popular Culture